2011
DOI: 10.1007/s10616-011-9375-4
|View full text |Cite
|
Sign up to set email alerts
|

Generation of functional monocyte-derived fast dendritic cells suitable for clinical application in the absence of interleukin-6

Abstract: To develop dendritic cells (DCs)-based immunotherapy for cancer patients, it is necessary to have a standardized, reproducible, fast, and easy to use protocol for in vitro generation of fully functional DCs. Recently, a new strategy was described for differentiation and maturation of human monocyte (Mo)-derived fast-DCs with full T cell stimulatory capacity within only 48-72 h of in vitro culture. Interleukin (IL)-6 plus tumour necrosis factor (TNF)-a, IL-1b, and prostaglandin (PG)-E 2 were used in this strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Dauer and colleagues on 2003 described a strategy for differentiation and maturation of monocyte derived DC within only 48-72 h of in vitro culture, called "Fast" protocol, and several other groups have further elaborated on this pioneering work [13][14][15][16][17]. Here we described this method modified from our group to obtain Fast mature autologous DC, loaded with antigens obtained from whole tumor lysate, suitable for the immunotherapy of glioblastoma patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dauer and colleagues on 2003 described a strategy for differentiation and maturation of monocyte derived DC within only 48-72 h of in vitro culture, called "Fast" protocol, and several other groups have further elaborated on this pioneering work [13][14][15][16][17]. Here we described this method modified from our group to obtain Fast mature autologous DC, loaded with antigens obtained from whole tumor lysate, suitable for the immunotherapy of glioblastoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…Fully mature DC are generally obtained in 7-10 days of culture: differentiation step take place in 5-7 days with GM-CSF and IL4; immature DC are subsequently induced to maturation for 1-3 days with pro-inflammatory stimuli to generate a population of immunogenic mature DC [12]. Several groups have shown that it is possible to obtain mature DC in 2-3 days cell culture [13][14][15][16][17]. The in vitro generation of DC with Fast protocol will shorten the time from the patients' recruiting to DC treatment and therefore be beneficial in the clinical setting: a Fast protocol would result in a simplified processing that minimizes inter-preparations variability and the risk of contamination, also resulting less expensive.…”
Section: Introductionmentioning
confidence: 99%
“…‘FastDCs’ have been obtained after mere 2-day culturing periods and retain the essential ability to induce antigen-specific T-cell responses [33, 34]. Important differences of fastDCs compared to standard DCs include higher yields in culture, lower release of IL-12 p70, higher CCL19-induced chemokinesis, better intracellular antigen processing, and more effective priming of tumor-specific cytotoxic T-cells [33, 35, 36].…”
Section: Dendritic Cell Generation In-vitromentioning
confidence: 99%
“…(Note that KLH antibody levels in our ELISA system are about 10-fold higher than AChR antibody levels). selective culture (Jones et al, 2012), (Ramadan, 2011), and newer methods of deriving large quantities of DCs from iPS cells are promising (Senju et al, 2010). Fortunately, mature human DCs are not vulnerable to killing by FasL (Ashany et al, 1999;Hoves et al, 2003), and should therefore be well suited for this purpose.…”
Section: Dendritic Cells As "Guided Missiles"mentioning
confidence: 99%